SABAR DALAM HADIS - Salewe, M. Idman (Department of Hadis Sciences (IH), Faculty of Usuluddin, Adab, and Da'wah (FUAD), State Islamic Institute of Langsa (IAIN), 2018)
This article discourse about the meaning of patient, as well as the concept of patience in hadith. The discussion conducted by using maw??'? method and takhr?j method throughpronunciations, which collects hadith from word sabara or or other keywords related to it. Author found that hadith about the patient classified as a weak hadith, because there was a narrator who mubham. From the aspect of matan, hadith on patient does not contain sy?? and ?illah. Patient is a struggle that illustrates the power of the soul culprit (controlling) the passion of lust, so that for every Muslim having the character of patient in anycircumstances. Patient has a close aspect with faith, piety, and good deeds. A patient is someone who is optimistic in facing of difficulties and problems in their life. A patient people are those who fear to Allah, and those who continue to be active in doing good deeds is a piety one.